2014
DOI: 10.1055/s-0034-1370694
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Intraforaminal Synovial Cyst in Young Adulthood: Case Report and Review of the Literature

Abstract: Study Design Case report. Objective Lumbar juxtafacet cysts (synovial and ganglion cysts) are a rare cause of low back and radicular leg pain. Most patients with lumbar cysts are in their sixth decade of life and have significant facet joint and disk degeneration. Lumbar synovial cysts (LSCs) are extremely rare in adolescence and young adulthood, and to our knowledge, only two pediatric cases of LSC have been reported in the literature. We aim to prove the existence of LSC in adolescent patients as a real enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The rate of CSF leakage in Literature ranges from 3.1% to 12.66%. 18,19 Leakage of CSF carries the risk for wound healing problems, longer hospital stay and may lead to further surgical procedures. Moreover, Kothe et al 14 revealed a potential inferior outcome in terms of low back pain after 12 months in the case of dural leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of CSF leakage in Literature ranges from 3.1% to 12.66%. 18,19 Leakage of CSF carries the risk for wound healing problems, longer hospital stay and may lead to further surgical procedures. Moreover, Kothe et al 14 revealed a potential inferior outcome in terms of low back pain after 12 months in the case of dural leakage.…”
Section: Discussionmentioning
confidence: 99%
“…This is concordant to the literature. The rate of CSF leakage in Literature ranges from 3.1% to 12.66% 18,19…”
Section: Discussionmentioning
confidence: 99%
“…FJ synovial cysts as a cause of LBP with radicular symptoms is an uncommon finding. The overall incidence of anterior facet synovial cysts is reported to be 2.3% [4]. The incidence of facet joint synovial cysts is increasing due to greater availability of imaging modalities such as MRI and an increase in the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…LSC are thought to form when facet joint (FJ) degeneration allows for fluid build-up in the joint, which escapes the joint capsule and forms cysts in the synovium [2] [3] [4] [5] [6]. Symptomatic LSC are most often found posterior and lateral to the dural sac, anterior to the FJ [6].…”
Section: Introductionmentioning
confidence: 99%
“…4,10 However, there are reports of spontaneous regression of such cysts, 7,11 as well as intradural invasion 12 or spontaneous hemorrhage causing a cauda equina syndrome or bilateral foot drop. 13,14 The clinical symptoms can differ and are difficult to predict.…”
Section: Introductionmentioning
confidence: 99%